Can the Neutrophil/Lymphocyte*Platelet Ratio Predict Acute Appendicitis? An Analytical Study - Abuzer ÖZKAN; Serdar ÖZDEMİR; Hatice Şeyma AKÇA; Muhammed Tahir AKÇA (Namık Kemal Tıp Dergisi, 2024)

(untitled)
Aim: Our primary aim is to determine whether the neutrophil/lymphocyte*platelet ratio (NLPR) has the ability to predict acute appendicitis. Our secondary aim is to show whether the NLPR is effective in differentiating complicated and non-complicated acute appendicitis. Materials and Methods: Our study was planned retrospectively, and patients over 18 years of age who were diagnosed with acute appendicitis and admitted to the Health Sciences University Turkey, Ümraniye Training and Research Hospital between 01.04.2022 and 01.04.2023, were included in the study. Results: A total of 492 patients were included in our study, and 242 (49.18%) of them were diagnosed with acute appendicitis. Neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR) and NLPR were statistically significantly higher in patients with acute appendicitis compared to the control group (p<0.001, p<0.001, p<0.001, respectively) (the area under the curve was 0.96, 0.70, 0.94, respectively). Conclusion: NLR, PLR and NLPR can be used as predictors for the diagnosis of acute appendicitis, but according to our study, NLR, PLR and NLPR should not be used as prognostic indicators of acute appendicitis.